Suppose f and g are differentiable functions such that
x g ( f ( x ) ) f ′ ( g ( x ) ) g ′ ( x ) = f ( g ( x ) ) g ′ ( f ( x ) ) f ′ ( x )
∀ x ∈ ℜ and
∫ 0 a f ( g ( x ) ) d x = 2 1 − e − 2 a ∀ a ∈ ℜ .
Given that g ( f ( 0 ) ) = 1 and if the value of g ( f ( 4 ) ) = e − 4 k , where k is a natural number, then find k .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wow!
I was stuck there integrating the first step and then applying it somewhere, but actually i didn't need to integrate that.
Rightly Judged.
Problem Loading...
Note Loading...
Set Loading...
The differential equation can be written as d x d [ ln ( g ( f ( x ) ) ) ] = x d x d [ ln ( f ( g ( x ) ) ) ] and, differentiating the integral formula, we know that f ( g ( x ) ) = e − 2 x , and so d x d [ ln ( g ( f ( x ) ) ) ] = − 2 x so that ln ( g ( f ( x ) ) ) = − x 2 , and hence g ( f ( x ) ) = e − x 2 . We see that we have f ( x ) = x 2 and g ( x ) = e − x .
Thus g ( f ( 4 ) ) = e − 1 6 ,which makes k = 4 .